PENGARUH KECERDASAN EMOSIONAL, MOTIVASI KERJA DAN EMPLOYE ENGAGEMENT TERHADAP KINERJA KARYAWAN PT.J&T EXPRESS SEPATAN - Santi Susanti (Bajang Institute, 2025)
Employees who are able to manage and understand their own emotions as well as the emotions of others tend to perform better. Apart from that, employees who have high motivation, especially those who feel their needs for appreciation and selfactualization are met, show increased performance in carrying out their daily tasks. By encouraging a high level of engagement, it reflects the dedication, enthusiasm and commitment of employees, especially those in this research, namely J&T couriers in carrying out their duties. Finding out how EQ, intrinsic drive, and teamwork affect J&T couriers' productivity was the driving force behind this research. Additionally, it looked at workplace engagement, emotional intelligence, and job motivation to see whether there were any elements that helped or hurt courier performance improvement. A purposive sample strategy was used to pick respondents, with questionnaires being distributed to 106 employees. A value of 0.621 for R-squared (R2) was displayed in the results. The strong correlation between J&T courier performance and EQ, intrinsic motivation at work, and employee engagement provides an explanation.